Spiritual episteme: sensemaking in the framework of organizational spirituality - Izak, Michal (Journal of organizational change management, 2012)
Purpose - The purpose of this research is to enable the examination of sensemaking mechanisms, inherent in the discourse of organizational spirituality (OS), which embed meanings this discourse creates. In order to achieve this goal the paper explores the pivotal notion of "spirituality" in OS, examines the conditions of emergence of its main characteristics, and inquires into OS participants' mental processes which help to sustain it. Thus, the conceptual space is critically explored in which organizational actors make their commitments to attain goals by spiritual means and in which the alleged causal mechanisms operate.Design methodology approach - The approach taken is a critical analysis of literature and empirical material.Findings - The logic of OS conceptual framework is vastly inconsistent with rationalism, which underpins typical functionalist assertions of OS proponents. The central OS notion - spirituality - lacks concrete and independent characteristics. It can be perceived as a mere classification tool which groups together certain "positive" phenomena, perspectives or outcomes. The legitimacy of this operation within the discourse is guaranteed by its episteme - the set of rules, which makes certain moves possible and excludes some others. It may easily enforce or preclude the particular interpretations of organizational reality or validity of certain initiatives. The latter hints at the political dimension of OS.Research limitations implications - Potential researchers should be sensitive to the issues of logical circularity of OS discourse and its degree of incoherence with rationalist assumptions. The design of research on OS should attempt to delve into meanings created by OS discourse profiting from proximity to research subjects ensured by careful application of qualitative methods. Research could focus more on the political dimension: issues of power relations; methods of exerting influence; gaining support, etc., instead of contemplating more vague territories which OS studies seem inclined to explore. These results refer to a limited number of participants and organizations and are not fully generalizable, which is inevitable in qualitative research. The geographical concentration of the research sample might have affected the results to some extent, however this fact is innocuous to the overall validity of this study.Originality value - Beyond the scope of many recent papers that emphasize the positive role of organizational spirituality as a means of attaining particular objectives, the paper offers an alternative approach in which OS makes such calculations very difficult, and yet creates conditions which are conducive to advancing OS participants' political agendas.